(NkALINOWA MR)QÆQ (B:s)E (NPOEZ)QÆÇ (B/s)E - (NmAR^UK(B, (NdOMKA wASIL)QÆWNA(B.s)E ((N~ERN)QÆWCÆ (B:s)E (NqWORSXKIJ s(B. (Nn(B.,s, 2010)
(Nu ZB)QÆRKU WWÆJ[LI POEZÆÇ SAMOBUTNXOÇ BUKOWINSXKOÇ POETESI dOMKI mAR^UK(B. çç (NPOEZÆQ (B- (NCE ÆSTORÆQ VITTQ NARODU(B, (NZ QKOGO WONA WIJ[LA(B, Æ (NQKIJ WONA L@BITX WSÆÃ@ DU[O@(B.s)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQ(B.s)E